Caffeine's Influence on Nicotine's Effects in Nonsmokers - Blank, Melissa D. (2007)
OBJECTIVE: To determine if nicotine's effects are influenced by caffeine in nonsmoking, moderate-caffeine consuming individuals (N=20). METHODS: The first 3 sessions included one of 3 randomly ordered, double-blind caffeine doses (0, 75, or 150 mg, oral [po]) and 2 single-blind nicotine gum doses (2 and 4 mg) in ascending order. The fourth session (single blind) repeated the 0 mg caffeine condition. RESULTS: Nicotine increased heart rate and subjective ratings indicative of aversive effects, and decreased reaction times. These effects were independent of caffeine dose and reliable across sessions. CONCLUSIONS: In nonsmokers, nicotine effects are not influenced by moderate caffeine doses.